Adubação nitrogenada e potássica na produtividade e qualidade de minimilho para conserva - Favarão, Simone Correia Molina (2011)
The baby corn is the inflorescence of maize (spikelet) prior to fertilization and early grain formation. With regard to the management, the cultivation is carried out with directions available for production of corn grain. As the baby corn is harvested in the young, it is assumed that the need for fertilizer especially nitrogen and potassium are lower. Given the above, the present study was to evaluate agronomic characteristics and attributes of baby corn post-harvest due to different levels of nitrogen and potassium cultivated in the region of Maringá - PR, summer and winter crops in the agricultural year 2010/2011. The experiment was conducted at the Experimental Farm of Iguatemi - FEI, in Maringá, Northwest Paraná, the trial period matched the two seasons, summer and winter of 2010/2011 crop year. The design was randomized blocks in factorial scheme 4x4, with four levels of nitrogen (0, 50, 75 and 100 kg ha-1) and four potassium levels (0, 20, 40 and 60 kg ha-1), applied 50% at sowing and 50% coverage in the V6 stage of development. The plant material used was a simple hybrid corn popcorn breeding program of UEM. After harvesting agronomic traits were evaluated: number, diameter, length and weight of commercial desempalhadas spikelets. They were then prepared and canned after about 4 months, these were assessed for pH of the brine, pH of corn, soluble solids, moisture, ash, fiber, carbohydrates, lipids, proteins, color and texture. The results were analyzed by analysis of variance with probability at 5% level of significance by F test and the statistical program SISVAR for comparison of means was the mean test Student-Newman-Keuls at 5% probability. The highest yields were obtained in the summer season. The control (00N-00K) showed yield kg ha-1 significantly lower than others in both harvests. Regarding the nutritional characteristics of all values found were consistent with those found in the literature and did not represent different nutritional gain in order that we can recommend treatment (fertilizer application) as a function of nutritional valeus.